Contact material for vacuum valve, vacuum valve, and method of manufacturing contact material for vacuum valve

A copper-molybdenum-vanadium sintered contact material for vacuum valves addresses high costs and performance issues by controlling oxygen content and density, enhancing current blocking efficiency and reducing manufacturing complexity.

JP2025015268APending Publication Date: 2025-01-30KK TOSHIBA +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023118577
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Existing vacuum valve electrode materials, particularly copper-chromium alloys, face issues with high costs, complex manufacturing processes, and compromised performance due to residual oxygen and sintering density problems, leading to increased costs and inefficiencies.

Method used

A contact material for vacuum valves comprising a copper matrix with molybdenum and chromium or vanadium, sintered using a hydrogen reduction method to control oxygen content and achieve uniform distribution, resulting in a low-cost material with excellent current blocking characteristics.

Benefits of technology

The proposed material achieves low residual oxygen content (10-1000 ppm) and high sintering density (90-99.9%), ensuring effective current blocking with improved manufacturing efficiency and reduced costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015268000001_ABST
    Figure 2025015268000001_ABST
Patent Text Reader

Abstract

To provide a contact material for a vacuum valve with good current interruption properties at low cost.SOLUTION: A contact material for a vacuum valve includes a sintered alloy containing a copper matrix, a filler containing molybdenum, and at least one sintering aid of chromium or vanadium.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE The present invention relates to a contact material for a vacuum valve, a vacuum valve, and a method for manufacturing a contact material for a vacuum valve. [Background technology]

[0002] The need for larger capacity vacuum circuit breakers is growing, so there is a demand for improved vacuum valve performance. A vacuum valve is a cylindrical insulating container made of insulating material, with both ends sealed with metal flanges, and a high vacuum is maintained inside the insulating container. A pair of electrodes integrated with the flanges via bellows are connected to the circuit breaker operating mechanism and can move in the axial direction of the vacuum valve. In the event of a fault current, the fault current can be interrupted by opening the electrodes.

[0003] Copper-chromium alloys are used as electrode materials for vacuum valves. There are three types of copper-chromium alloys, which are made by different methods: melting, sintering, and infiltration, and each has its own characteristics. Molten materials are manufactured by melting the material in a vacuum atmosphere, then casting and quenching it. Due to the degassing effect in the vacuum and the quenching in the mold, there is little residual oxygen, and it has a metal structure with fine and uniformly dispersed chromium of about 10 μm in the copper matrix. Since it is quenched in the final process, there is a limit to the weight that can be melted at one time in order to maintain a constant cooling rate, so it is generally expensive, but it has the best electrical performance.

[0004] Sintered materials are manufactured by sintering a green compact made by mixing and molding material particles in a vacuum or in a reducing or inert atmosphere. Since it is thermodynamically impossible to reduce chromium oxide using a vacuum or a reducing or inert atmosphere in the sintering process of copper-chromium alloys, a large amount of oxygen remains in the sintered material, which deteriorates the current interrupting capacity in particular. In addition, if the sintered density is low, the molten brazing material will penetrate into the internal pores during manufacturing, which can easily cause manufacturing defects. However, the cost is low because many green compacts can be sintered at once.

[0005] Infiltrating materials are manufactured by preparing a low-density sintered body of chromium, and then infiltrating molten copper into the low-density sintered body. The flow of molten copper expels the chromium oxide layer on the surface of the sintered body of chromium, reducing the amount of residual oxygen to the same level as that of the melted material. However, since the low-density sintered body of chromium has a minimum density at which it can maintain its structure, it is not possible to manufacture a copper-chromium alloy with a chromium content of approximately 40% by weight or less. In addition, since copper containing a large amount of impurities such as oxygen is discharged, the efficiency of raw material use is low and the cost is high. Each type has its own advantages and disadvantages, so it is necessary to use different applicable ratings for each manufacturing method. However, handling multiple types of products brings with it challenges such as further increases in costs and the complication of manufacturing lines and methods. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 3597544 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of an embodiment of the present invention is to provide a contact material for a vacuum valve that is low cost and has excellent current interruption characteristics. [Means for solving the problem]

[0008] According to an embodiment, there is provided a contact material for a vacuum valve, comprising a sintered alloy containing a copper matrix, a filler containing molybdenum, and a sintering aid of at least one of chromium and vanadium. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a model diagram showing a part of a cross-sectional structure of a vacuum interrupter contact material according to a first embodiment. [Diagram 2] FIG. 11 is a vertical cross-sectional view illustrating the configuration of a vacuum interrupter according to a second embodiment. [Diagram 3] FIG. 11 is a flow diagram showing an example of a method for producing a contact material for a vacuum interrupter according to a third embodiment. [Figure 4] FIG. 11 is a flow chart showing another example of the method for producing a contact material for a vacuum interrupter according to the third embodiment. [Diagram 5] FIG. 1 is a model diagram showing an example of a cross-sectional structure of a vacuum interrupter contact material according to a first embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments will be described with reference to the drawings. The disclosure is merely an example, and appropriate modifications that are within the spirit of the invention and that can be easily conceived by a person skilled in the art are naturally included in the scope of the present invention. In addition, in order to make the explanation clearer, the width, thickness, shape, etc. of each part may be shown diagrammatically compared to the actual embodiment, but these are merely examples and do not limit the interpretation of the present invention. In this specification and each figure, elements similar to those described above with respect to the previous figures may be given the same reference numerals, and detailed explanations may be omitted as appropriate.

[0011] According to the embodiments, there are provided a vacuum interrupter contact material according to a first embodiment, a vacuum interrupter according to a second embodiment, and a method for producing a vacuum interrupter contact material according to a third embodiment. The contact material for a vacuum valve according to the first embodiment includes a sintered alloy containing a copper (Cu) matrix, a filler containing molybdenum (Mo), and a sintering aid of at least one of chromium (Cr) and vanadium (V). The Cu matrix is ​​a base material whose main component is copper, and can contain, as a secondary component, a solid solution with the sintering aids Cr and / or V. Here, the main component refers to the component that is contained in the greater amount among the components that make up the Cu matrix.

[0012] According to the first embodiment, a contact material for a vacuum interrupter having excellent current interruption characteristics can be obtained at low cost. FIG. 1 shows a model diagram illustrating a part of the cross-sectional structure of a vacuum interrupter contact material according to the first embodiment. The contact material 20 for a vacuum valve includes a multi-phase sintered alloy containing a Cu matrix 21, a filler 22 dispersed in the Cu matrix 21, and at least one sintering aid of Cr or V. In FIG. 1, an example of the filler 22 is shown in an enlarged scale.

[0013] The filler 22 may have a volume-based median diameter of 0.01 μm to 5 μm. The filler 22 is dispersed in the Cu matrix 21, and at least a part of Mo in the filler 22 may form a solid solution with the sintering aids Cr and / or V. At this time, Mo and Cr and / or V may form a solid solution with their thermodynamic maximum value as the upper limit.

[0014] The Cu matrix 21 can be solid-soluble with the sintering aids Cr and / or V in the region 23 surrounding the filler 22. For example, in a region ranging from the boundary surface 25 of the filler 22 to about 0.5 μm, Cu and Cr and / or V can be solid-soluble with their thermodynamic maximum values ​​as the upper limit. Outside the region 23 ranging from the boundary surface 25 with the Mo filler 22 to a maximum of 0.5 μm, the Cu matrix 21 can be pure Cu with a purity of 99.6% or more.

[0015] The oxygen content of the sintered alloy can be in the range of 10 ppm to 1000 ppm. When the oxygen content is in this range, a vacuum valve contact material with better current interruption properties can be obtained. It is difficult to reduce the oxygen content to less than 10 ppm, and when the oxygen content exceeds 1000 ppm, the current interruption properties tend to deteriorate. The sintered alloy can be formed by sintering material particles. The sintered alloy can be porous and the relative density can be 90 to 99.9%. The sintered alloy including the Cu matrix 21 and the filler 22 having the structure shown in FIG. 1 can have a uniform and finely dispersed structure, as can be obtained by the manufacturing method of the melting material.

[0016] As the material particles, for example, sintering aid particles Cr and / or V can have a volume-based median diameter of 50 to 200 μm before sintering. If the diameter is less than 50 μm, the amount of oxygen derived from the raw material increases due to an increase in the specific surface area, exceeding the deoxidizing ability in the subsequent process. If the diameter exceeds 200 μm, it cannot be completely dissolved in the Cu matrix in the sintering process, and the structure after sintering becomes coarse. In addition, Mo particles can have a volume-based median diameter of 0.01 to 10 μm. It is difficult to manufacture Mo particles less than 0.01 μm, and if the diameter exceeds 10 μm, the structure after sintering becomes coarse, tending to deteriorate the current interruption characteristics.

[0017] The Cu content can be 75 to 85% by weight based on the total weight of the sintered alloy. The total content of Mo and the content of Cr and / or V can be 15 to 25% by weight based on the total weight of the sintered alloy. If it is less than 15% by weight, the dielectric breakdown characteristics tend to deteriorate, and if it exceeds 25% by weight, the current interruption characteristics tend to deteriorate. The Mo content and the Cr and / or V content can be freely changed within the above-mentioned combined range while taking into consideration the dielectric breakdown characteristics and current interruption characteristics. The vacuum valve according to the second embodiment is provided with an electrode including a contact made of a vacuum valve contact material including a Cu matrix, a filler containing Mo, and a sintered alloy containing at least one sintering aid of Cr or V.

[0018] FIG. 2 is a vertical cross-sectional view showing the configuration of a vacuum interrupter according to the second embodiment. As shown in the figure, the vacuum valve 100 has openings at both ends and is provided with a cylindrical ceramic container 1 made of, for example, alumina porcelain, a fixed sealing metal fitting 2 sealed to one opening, and a movable sealing metal fitting 3 sealed to the other opening. A vacuum is maintained inside the vacuum valve 100. The fixed sealing metal fitting 2 has a central opening through which a fixed current-carrying shaft 4, which serves as one of the electric paths, is fixed. A fixed electrode 5 is fixed to the end of the fixed current-carrying shaft 4 inside the ceramic container 1. A fixed contactor 6 is fixed to the end face of the fixed electrode 5, thereby forming a joint structure between the fixed electrode 5 and the fixed contactor 6. A movable contactor 7, which faces the fixed contactor 6 and serves as a pair of detachable contacts, is fixed to the end face of the movable electrode 8, thereby forming a joint structure between the fixed contactor 6 and the movable contactor 7. The movable electrode 8 is fixed to the end of a movable current-carrying shaft 9, which serves as another electric path and movably passes through a central opening provided in the movable sealing metal fitting 3. Here, the vacuum valve contact material according to the first embodiment can be used as the contacts for the fixed contactor 6 and the movable contactor 7.

[0019] The part of the movable current-carrying shaft 9 on the movable sealing metal fitting 3 side from the center part is the part that is led out of the ceramic container 1, and a bellows cover 10 for airtight sealing is provided at that part, and one end of a cylindrical bellows 11 that can expand and contract is disposed on the bellows cover 10. The other end of the bellows 11 is sealed to the central opening of the movable sealing metal fitting 3. This allows the movable current-carrying shaft 9 to move in the axial direction while maintaining the vacuum in the insulating container 1. A cylindrical arc shield 12 is provided around the fixed electrode 5, the movable electrode 8, the fixed contactor 6, and the movable contactor 7 to prevent metal vapor and molten metal generated during opening and closing from adhering to the inner wall of the insulating container 1 and reducing the insulation resistance. According to the second embodiment, by using the vacuum interrupter contact material according to the first embodiment as the contacts, it is possible to obtain a vacuum interrupter having excellent current interruption characteristics at low cost.

[0020] FIG. 3 shows a flow diagram illustrating an example of a method for producing a contact material for a vacuum interrupter according to the third embodiment. As shown in the figure, the manufacturing method of the contact material for the vacuum valve of the third embodiment includes compressing a mixture of material particles including copper particles, Mo particles, and sintering aid particles of at least one of Cr and V to form a green compact (ST1), heating the green compact in a hydrogen atmosphere (ST2), and sintering the heated green compact (ST3) to form a sintered body.

[0021] According to the manufacturing method of the contact material of the vacuum valve according to the third embodiment, the surface oxide film of the material particles, particularly Mo particles, can be reduced and removed by heating the green compact containing the mixture of material particles in a hydrogen atmosphere (ST2). This makes it possible to reduce the oxygen content in the obtained sintered alloy to a low concentration, for example, in the range of 10 ppm to 1000 ppm, and a contact material for a vacuum valve with excellent current interruption characteristics can be obtained. Furthermore, by removing the surface oxide film of the material particles, when the heated green compact is further sintered (ST3), as shown in FIG. 1, Cr and / or V used as sintering aids and Mo filler 22, and Cr and / or V and Cu matrix 21 are each likely to form a solid solution. This results in a multi-phase sintered alloy containing Cu matrix 21, filler 22 dispersed in Cu matrix 21, and at least one sintering aid of Cr or V. Although this multi-phase sintered alloy is formed by a relatively low-cost manufacturing method of sintered material, it can have a uniform and fine dispersion structure compared to sintered materials obtained by a manufacturing method of melted material, and has good current interruption characteristics.

[0022] On the other hand, if the mixture of material particles is not heated in a hydrogen atmosphere (ST2), the oxygen content of the sintered alloy tends to be high because the surface oxide film of the material particles is not removed. If the surface oxide film of the material particles is not removed, when the heated green compact is further sintered, the Mo filler and Cu matrix will not easily form a solid solution with the Cr and / or V used as sintering aids, and the sintered alloy will have Cu particles, Mo particles, Cr particles and / or V particles dispersed therein, making it difficult to obtain a multi-phase sintered alloy as shown in Figure 1.

[0023] The heating temperature in the hydrogen atmosphere can be 300 to 500° C. If the temperature is less than 300° C., the reduction reaction by hydrogen is insufficient and the oxygen content tends to be unable to be reduced, whereas if the temperature exceeds 500° C., sintering of the material particles progresses, making it difficult for hydrogen to enter between the material particles, and therefore the reduction of the surface oxide film of the material particles by the hydrogen atmosphere tends to be insufficient. The heating time in the hydrogen atmosphere can be 3 to 5 hours. If it is less than 3 hours, the reduction reaction by hydrogen is insufficient and the oxygen content tends not to be reduced, whereas if it exceeds 5 hours, the reduction reaction proceeds sufficiently, which increases the process cost. The hydrogen atmosphere may be high-purity hydrogen gas. After the mixture of material particles is heated in the hydrogen atmosphere, the hydrogen atmosphere may be replaced with an inert gas. For example, nitrogen may be used as the inert gas.

[0024] The sintering temperature of the green compact can be 1000 to 1400° C. If the temperature is less than 1000° C., the sintered density tends to be low, and if the temperature exceeds 1400° C., the shape after sintering tends to be significantly deformed. The sintering time of the green compact can be 3 to 10 hours. If it is less than 3 hours, the sintered density tends to be low, and if it exceeds 10 hours, the sintering has progressed sufficiently, so that the process cost tends to increase.

[0025] Sintering of the green compact can be carried out in two or more stages. For example, in the case of sintering in two stages, the first sintering temperature of the green compact in the first stage can be 900 to 1050°C. Outside this range, the sintered density of the final sintered body tends to decrease. Furthermore, the first sintering time of the green compact can be 3 to 5 hours. Outside this range, the sintered density of the final sintered body tends to decrease. In the second stage, after the first stage sintering, further compaction can be performed at a second pressure higher than the first pressure at which the green compact was initially formed, for example, the first pressure can be 1-100 MPa and the second pressure can be 100-500 MPa.

[0026] The second sintering temperature of the green compact may be 1100 to 1400°C. Outside this range, the sintered density tends to decrease. The second sintering time of the green compact may be 3 to 10 hours. Outside this range, the sintered density tends to decrease. In this way, according to the manufacturing method for the contact material of the vacuum valve of the third embodiment, it is possible to achieve both the low residual oxygen content and uniform fine dispersion structure of the molten material and the low cost of the sintered material, and it is possible to obtain a contact material for a vacuum valve with good current interruption characteristics at low cost.

[0027] The following examples are provided to more specifically explain the embodiments. Working Example Comparative Example 1 (Example of General-Purpose Material Ingot) A Cu75 wt%-Cr25 wt% ingot manufactured by melting method as a contact material for a general-purpose vacuum valve was machined into a disk shape by cutting, and applied to the fixed contact 6 of the fixed electrode 5 and the movable contact 7 of the movable electrode 8, respectively, as in the vacuum valve shown in FIG. 2. The fixed electrode 5, the movable electrode 8, the arc shield 12, and the insulating container 1 were silver brazed to produce a vacuum valve having a configuration similar to that of the vacuum valve 100 shown in FIG. 2. The maximum breaking current value and maximum breakdown voltage were measured using this vacuum valve. The maximum breakdown voltage and maximum breaking current of the general-purpose electrode material Cu75 wt%-Cr25 wt% of Comparative Example 1 are set to 1, and each value in the following Comparative Examples and Examples is a standard value. In addition, the residual oxygen amount was measured by inert gas fusion-infrared absorption method and was 200 ppm. Although the performance as a contact material for a vacuum valve is good, the melting method is expensive, so the overall evaluation was poor ×.

[0028] Comparative Example 2 (Example of a sintered body made of a general-purpose material) A Cu75% by weight-Cr25% by weight sintered body manufactured by a melting method as a contact material for a general-purpose vacuum valve was machined into a disk shape by cutting, and was applied to the fixed contact 6 of the fixed electrode 5 and the movable contact 7 of the movable electrode 8, respectively, as in the vacuum valve shown in FIG. 2. The fixed electrode 5, the movable electrode 8, the arc shield 12, the insulating container 1, etc. were silver brazed to produce a vacuum valve having a configuration similar to that of the vacuum valve 100 shown in FIG. 2. The maximum interrupting current value was measured using this vacuum valve in the same manner as in Comparative Example 1, and was 0.7. The dielectric breakdown voltage was 0.8. The amount of residual oxygen was measured by the inert gas fusion-infrared absorption method, and was 1200 ppm. Since the performance as a contact material for a vacuum valve was inferior to that of Comparative Example 1, the overall evaluation was poor x.

[0029] Example 1 (Example of Cu75wt%-Cr5wt%-Mo20wt% hydrogen reduction sintering method) FIG. 4 shows a flow diagram illustrating a method for producing a contact material for a vacuum interrupter according to Example 1, as another example of a method for producing a contact material for a vacuum interrupter according to the third embodiment. As shown in Fig. 4, in the manufacturing method of the contact material of the vacuum valve according to the first embodiment, first, electrolytic Cu powder having a particle size of 45 μm (here, the median diameter based on volume), electrolytic Cr powder having a particle size of 75 μm, and Mo powder having a particle size of 3 μm were used as raw material particles. The material particles were weighed to be Cu 75 wt%-Cr 5 wt%-Mo 20 wt% and mixed in a ball mill for 3 hours (ST11). After mixing, the mixture was filled into a die mold and pressed at 50 MPa to form a green compact (ST12). The bulk density of the green compact was 53%.

[0030] The green compact was placed in a resistance heating furnace filled with high-purity hydrogen gas, heated at 500°C for 5 hours, and then cooled to 100°C (ST13). Next, the furnace was purged with nitrogen, and then cooled for 10 -3 The material was evacuated to a vacuum of the order of Pa (ST14). It was then heated at 1000°C for 5 hours (ST15). The density of the sintered body after heating was 80%. Next, the sintered body was placed in a die and pressed at 400 MPa (ST16). The density of the sintered body after pressing was 87%.-3 The sintered body was placed in a resistance heating furnace set to a vacuum level of the Pa range and heated at 1200°C for 5 hours to obtain a sintered alloy as the sintered body (ST17). The density of the sintered body after heating was 98%. A part of the sintered body was cut, and the cross section was observed and analyzed using a scanning electron microscope and an energy dispersive X-ray detector.

[0031] As an example of the cross-sectional structure of the vacuum interrupter contact material according to the first embodiment, a model diagram showing the cross-sectional structure of a portion of the sintered body of Example 1 is shown in FIG. As shown in Fig. 5, the cross-sectional image by the scanning electron microscope showed that the initial Cu particles derived from the material particles had disappeared and a Cu matrix 21-1 had been formed. The Mo particles 22-1 were dispersed in the Cu matrix 21-1 with a particle size of 0.01 µm to 1 µm. When the interface between the Mo particles 22-1 and the Cu matrix 21-1 was analyzed in detail by an energy dispersive X-ray detector, it was found that Cr was dissolved in the Mo particles 22-1, and that Cr was dissolved in a region up to 0.5 µm from the boundary surface between the Mo particles 22-1 and the Cu matrix 21-1, for example, a region corresponding to the region 23 with a distance d of 0.5 µm outward from the boundary surface 25 in the model diagram shown in Fig. 1.

[0032] No Cr was found in the area of ​​Cu matrix 21-1 farther away from the boundary surface than a distance d of 0.5 μm. The amount of residual oxygen was measured by inert gas fusion-infrared absorption method and found to be 300 ppm. The maximum interrupting current was measured by the same method as in the comparative example and found to be 1.6. The dielectric breakdown voltage was 1.2. The performance as a contact material for a vacuum valve was good, and the hydrogen reduction sintering method allows for mass production at low cost, so the overall evaluation was ○. The results are shown in Table 1 below.

[0033] Example 2 (Cu 75% by weight - V 5% by weight - Mo 20% by weight, example of hydrogen reduction sintering method) Electrolytic Cu powder with a particle size of 45 μm, V (vanadium) powder with a particle size of 45 μm, and Mo powder with a particle size of 3 μm were used as the raw material particles. The material particles were weighed to be Cu 75% by weight, V 5% by weight, and Mo 20% by weight, and mixed in a ball mill for 3 hours. After mixing, the mixture was filled into a die and pressed at 50 MPa to form a green compact. The bulk density of the green compact was 50%.

[0034] The green compact was placed in a resistance heating furnace filled with high-purity hydrogen gas, heated at 500°C for 5 hours, and then cooled to 100°C. The furnace was then purged with nitrogen and cooled for 10 -3 The sintered body was then evacuated to a vacuum of the order of 1000 Pa and heated at 1000°C for 5 hours. The density of the sintered body after heating was 70%. The sintered body was then placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 79%. -3 The sintered body was placed in a resistance heating furnace set to a vacuum level of the Pa range and heated at 1200°C for 5 hours to obtain a sintered alloy. The density of the sintered body after heating was 97%.

[0035] A part of the sintered body was cut and the cross section was observed and analyzed using a scanning electron microscope and an energy dispersive X-ray detector, and the initial V particles derived from the material particles had disappeared. Mo particles were dispersed with a particle size of 0.01 μm to 1 μm. A detailed analysis of the interface between the Mo particles and the Cu matrix revealed that V was dissolved in the Mo particles, and V was dissolved in the Mo particles in a region up to 0.05 μm from the boundary surface of the Cu matrix with the Mo particles. V was not observed in the region in the Cu matrix more than 0.05 μm away from the boundary surface. The amount of residual oxygen was measured by the inert gas fusion-infrared absorption method and found to be 400 ppm. The maximum interrupting current value was measured by the same method as in Comparative Example 1 and found to be 1.5. The dielectric breakdown voltage was 1.2. The performance as a contact material for a vacuum valve was good, and the hydrogen reduction sintering method allows for mass production and is low cost, so the overall evaluation was ○. The results are shown in Table 1 below.

[0036] Example 3 (Example of Cu75wt%-Cr1wt%-Mo24wt% hydrogen reduction sintering method) Electrolytic Cu powder with a particle size of 45 μm, Cr powder with a particle size of 75 μm, and Mo powder with a particle size of 3 μm were used as the raw material particles. The material particles were weighed to be Cu 75 wt%, Cr 1 wt%, and Mo 24 wt%, and mixed in a ball mill for 3 hours. After mixing, the mixture was filled into a die and pressed at 50 MPa to form a green compact. The bulk density of the green compact was 61%.

[0037] The green compact was placed in a resistance heating furnace filled with high-purity hydrogen gas, heated at 500°C for 5 hours, and then cooled to 100°C. The furnace was then purged with nitrogen and cooled for 10 -3 The sintered body was then evacuated to a pressure of the order of 1000 Pa and heated at 1000°C for 5 hours. The density of the sintered body after heating was 78%. The sintered body was then placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 84%. -3 The sintered body was placed in a resistance heating furnace set to a vacuum level of the Pa range and heated at 1300°C for 10 hours to obtain a sintered alloy. The density of the sintered body after heating was 98%.

[0038] A part of the sintered body was cut and the cross section was observed and analyzed using a scanning electron microscope and an energy dispersive X-ray detector, and the initial Cr particles derived from the material particles had disappeared. Mo particles were dispersed with a particle size of 0.01 μm to 1 μm. A detailed analysis of the interface between the Mo particles and the Cu matrix revealed that Cr was dissolved in the Mo particles, and that Cr was dissolved in the Mo particles in a region up to 0.05 μm from the boundary surface of the Cu matrix with the Mo particles. No Cr was found in the region in the Cu matrix more than 0.05 μm away from the boundary surface. The amount of residual oxygen was measured by the inert gas fusion-infrared absorption method and found to be 50 ppm. The maximum interrupting current value was measured by the same method as in the comparative example and found to be 1.4. The dielectric breakdown voltage was 1.15. The performance as a contact material for vacuum valves was good, and the hydrogen reduction sintering method allows for mass production at low cost, so the overall evaluation was ○. The results are shown in Table 1 below.

[0039] Example 4 (Cu 75% by weight - V 1% by weight - Mo 24% by weight, an example of hydrogen reduction sintering method) Electrolytic Cu powder with a particle size of 45 μm, V powder with a particle size of 45 μm, and Mo powder with a particle size of 3 μm were used as the raw material particles. The material particles were weighed to be Cu 75% by weight, V 1% by weight, and Mo 24% by weight, and mixed in a ball mill for 3 hours. After mixing, the mixture was filled into a die and pressed at 50 MPa to form a green compact. The bulk density of the green compact was 50%.

[0040] The green compact was placed in a resistance heating furnace filled with high-purity hydrogen gas, heated at 500°C for 5 hours, and then cooled to 100°C. The furnace was then purged with nitrogen and cooled for 10 hours. -3 The sintered body was placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 76%. Next, the sintered body was placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 76%. -3 The sintered body was placed in a resistance heating furnace set to a vacuum level of the Pa range and heated at 1300°C for 10 hours to obtain a sintered alloy. The density of the sintered body after heating was 97%.

[0041] A part of the sintered body was cut and the cross section was observed and analyzed using a scanning electron microscope and an energy dispersive X-ray detector, and the initial V particles derived from the material particles had disappeared. Mo particles were dispersed with a particle size of 0.01 μm to 1 μm. A detailed analysis of the interface between the Mo particles and the Cu matrix revealed that V was dissolved in the Mo particles, and V was dissolved in the Mo particles in a region up to 0.05 μm from the boundary surface of the Cu matrix with the Mo particles. V was not observed in the region in the Cu matrix more than 0.05 μm away from the boundary surface. The amount of residual oxygen was measured by the inert gas fusion-infrared absorption method and found to be 50 ppm. The maximum interrupting current value was measured by the same method as in the comparative example and found to be 1.4. The dielectric breakdown voltage was 1.1. The performance as a contact material for vacuum valves was good, and the hydrogen reduction sintering method allows for mass production and is low cost, so the overall evaluation was ○. The results are shown in Table 1 below.

[0042] Example 5 (Cu 80% by weight - Cr 1% by weight - Mo 19% by weight, example of hydrogen reduction sintering method) Electrolytic Cu powder with a particle size of 45 μm, Cr powder with a particle size of 75 μm, and Mo powder with a particle size of 3 μm were used as the raw material particles. The material particles were weighed to be Cu 75 wt%, Cr 1 wt%, and Mo 19 wt%, and mixed in a ball mill for 3 hours. After mixing, the mixture was filled into a die and pressed at 50 MPa to form a green compact. The bulk density of the green compact was 59%.

[0043] The green compact was placed in a resistance heating furnace filled with high-purity hydrogen gas, heated at 500°C for 5 hours, and then cooled to 100°C. The furnace was then purged with nitrogen and cooled for 10 -3 The sintered body was placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 80%. Next, the sintered body was placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 80%. -3 The sintered body was placed in a resistance heating furnace set to a vacuum level of the Pa range and heated at 1200°C for 5 hours to obtain a sintered alloy. The density of the sintered body after heating was 98%.

[0044] A part of the sintered body was cut and the cross section was observed and analyzed using a scanning electron microscope and an energy dispersive X-ray detector, and the initial Cr particles derived from the material particles had disappeared. Mo particles were dispersed with a particle size of 0.01 μm to 1 μm. A detailed analysis of the interface between the Mo particles and the Cu matrix revealed that Cr was dissolved in the Mo particles, and that Cr was dissolved in the Mo particles in a region up to 0.05 μm from the boundary surface of the Cu matrix with the Mo particles. No Cr was observed in the region in the Cu matrix more than 0.05 μm away from the boundary surface. The amount of residual oxygen was measured by the inert gas fusion-infrared absorption method and found to be 50 ppm. The maximum interrupting current value was measured by the same method as in the comparative example and found to be 1.8. The dielectric breakdown voltage was 1.1. The performance as a contact material for vacuum valves was good, and the hydrogen reduction sintering method allows for mass production at low cost, so the overall evaluation was ○. The results are shown in Table 1 below.

[0045] Example 6 (Cu 80% by weight - V 1% by weight - Mo 19% by weight, an example of hydrogen reduction sintering method) Electrolytic Cu powder with a particle size of 45 μm, V powder with a particle size of 45 μm, and Mo powder with a particle size of 3 μm were used as the raw material particles. The material particles were weighed to be Cu 80% by weight, V 1% by weight, and Mo 19% by weight, and mixed in a ball mill for 3 hours. After mixing, the mixture was filled into a die and pressed at 50 MPa to form a green compact. The bulk density of the green compact was 53%.

[0046] The green compact was placed in a resistance heating furnace filled with high-purity hydrogen gas, heated at 500°C for 5 hours, and then cooled to 100°C. The furnace was then purged with nitrogen and cooled for 10 hours. -3 The sintered body was placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 78%. Next, -3 The sintered body was placed in a resistance heating furnace set to a vacuum level of the Pa range and heated at 1300°C for 10 hours to obtain a sintered alloy. The density of the sintered body after heating was 97%.

[0047] A part of the sintered body was cut, and the cross section was observed and analyzed using a scanning electron microscope and an energy dispersive X-ray detector, and the initial V particles derived from the material particles had disappeared. Mo particles were dispersed with a particle size of 0.01 μm to 1 μm. A detailed analysis of the interface between the Mo particles and the Cu matrix revealed that V was dissolved in the Mo particles, and V was dissolved in the Mo particles in a region up to 0.05 μm from the boundary surface of the Cu matrix with the Mo particles. V was not observed in the region in the Cu matrix more than 0.05 μm away from the boundary surface. The amount of residual oxygen was measured by the inert gas fusion-infrared absorption method and found to be 90 ppm. The maximum interrupting current value was measured by the same method as in the comparative example and found to be 1.7. The dielectric breakdown voltage was 1.1. The performance as a contact material for vacuum valves was good, and the hydrogen reduction sintering method allows for mass production and is low cost, so the overall evaluation was ○. The results are shown in Table 1 below.

[0048] Example 7 (Cu 85% by weight - Cr 1% by weight - Mo 14% by weight, example of hydrogen reduction sintering method) Electrolytic Cu powder with a particle size of 45 μm, Cr powder with a particle size of 75 μm, and Mo powder with a particle size of 3 μm were used as the raw material particles. The material particles were weighed to be Cu 75 wt%, Cr 1 wt%, and Mo 14 wt%, and mixed in a ball mill for 3 hours. After mixing, the mixture was filled into a die and pressed at 50 MPa to form a green compact. The bulk density of the green compact was 62%.

[0049] The green compact was placed in a resistance heating furnace filled with high-purity hydrogen gas, heated at 500°C for 5 hours, and then cooled to 100°C. The furnace was then purged with nitrogen and cooled for 10 hours. -3 The sintered body was placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 88%. The sintered body was then heated at 1000°C for 5 hours. The density of the sintered body after pressing was 88%. -3 The sintered body was placed in a resistance heating furnace set to a vacuum of the Pa range and heated at 1200°C for 5 hours to obtain a sintered alloy. The density of the sintered body after heating was 99%.

[0050] A part of the sintered body was cut and the cross section was observed and analyzed using a scanning electron microscope and an energy dispersive X-ray detector, and the initial Cr particles derived from the material particles had disappeared. Mo particles were dispersed with a particle size of 0.01 μm to 1 μm. A detailed analysis of the interface between the Mo particles and the Cu matrix revealed that Cr was dissolved in the Mo particles, and that Cr was dissolved in the Mo particles in a region up to 0.05 μm from the boundary surface of the Cu matrix with the Mo particles. No Cr was observed in the region in the Cu matrix more than 0.05 μm away from the boundary surface. The amount of residual oxygen was measured by the inert gas fusion-infrared absorption method and found to be 40 ppm. The maximum interrupting current value was measured by the same method as in the comparative example and found to be 1.2. The dielectric breakdown voltage was 1.0. The performance as a contact material for vacuum valves was good, and the hydrogen reduction sintering method allows for mass production and is low cost, so the overall evaluation was ○. The results are shown in Table 1 below.

[0051] Example 8 (Cu85 weight - V1 weight - Mo14 weight Example of hydrogen reduction sintering method) Electrolytic Cu powder with a particle size of 45 μm, V powder with a particle size of 45 μm, and Mo powder with a particle size of 3 μm were used as the raw material particles. The material particles were weighed to be Cu 85% by weight, V 1% by weight, and Mo 14% by weight, and mixed in a ball mill for 3 hours. After mixing, the mixture was filled into a die and pressed at 50 MPa to form a green compact. The bulk density of the green compact was 50%.

[0052] The green compact was placed in a resistance heating furnace filled with high-purity hydrogen gas, heated at 500°C for 5 hours, and then cooled to 100°C. The furnace was then purged with nitrogen and cooled for 10 hours. -3 The sintered body was placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 75%. Next, the sintered body was placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 75%. -3 The sintered body was placed in a resistance heating furnace set to a vacuum level of the Pa range and heated at 1300°C for 10 hours to obtain a sintered alloy. The density of the sintered body after heating was 97%.

[0053] A part of the sintered body was cut and the cross section was observed and analyzed using a scanning electron microscope and an energy dispersive X-ray detector, and the initial V particles derived from the material particles had disappeared. Mo particles were dispersed with a particle size of 0.01 μm to 1 μm. A detailed analysis of the interface between the Mo particles and the Cu matrix revealed that V was dissolved in the Mo particles, and that V was dissolved in the Mo particles in a region up to 0.05 μm from the boundary surface of the Cu matrix with the Mo particles. V was not observed in the region in the Cu matrix more than 0.05 μm away from the boundary surface. The amount of residual oxygen was measured by the inert gas fusion-infrared absorption method and found to be 80 ppm. The maximum interrupting current was measured by the same method as in the comparative example and found to be 1.1. The dielectric breakdown voltage was 1.0. The performance as a contact material for vacuum valves was good, and the hydrogen reduction sintering method allows for mass production and is low cost, so the overall evaluation was ○. The results are shown in Table 1 below.

[0054] Example 9 (Cu 90% by weight - Cr 1% by weight - Mo 9% by weight, example of hydrogen reduction sintering method) Electrolytic Cu powder with a particle size of 45 μm, Cr powder with a particle size of 75 μm, and Mo powder with a particle size of 3 μm were used as the raw material particles. The material particles were weighed to be Cu 75 wt%, Cr 1 wt%, and Mo 9 wt%, and mixed in a ball mill for 3 hours. After mixing, the mixture was filled into a die and pressed at 50 MPa to form a green compact. The bulk density of the green compact was 69%.

[0055] The green compact was placed in a resistance heating furnace filled with high-purity hydrogen gas, heated at 500°C for 5 hours, and then cooled to 100°C. The furnace was then purged with nitrogen and cooled for 10 hours. -3 The sintered body was placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 86%. Next, the sintered body was placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 86%. -3 The sintered body was placed in a resistance heating furnace set to a vacuum of the Pa range and heated at 1200°C for 5 hours to obtain a sintered alloy. The density of the sintered body after heating was 99%.

[0056] A part of the sintered body was cut and the cross section was observed and analyzed using a scanning electron microscope and an energy dispersive X-ray detector, and the initial Cr particles derived from the material particles had disappeared. Mo particles were dispersed with a particle size of 0.01 μm to 1 μm. A detailed analysis of the interface between the Mo particles and the Cu matrix revealed that Cr was dissolved in the Mo particles, and that Cr was dissolved in the Mo particles in a region up to 0.05 μm from the boundary surface between the Mo particles and the Cu matrix. No Cr was observed in the region in the Cu matrix more than 0.05 μm away from the boundary surface. The amount of residual oxygen was measured by the inert gas fusion-infrared absorption method and found to be 30 ppm. The maximum interrupting current was measured by the same method as in the comparative example and found to be 0.9. The dielectric breakdown voltage was 0.9. Although the performance as a contact material for vacuum valves was somewhat inferior to that of Comparative Example 1, the hydrogen reduction sintering method allows for mass production and is low cost, so the overall evaluation was △. The results are shown in Table 1 below.

[0057] Example 10 (Cu 90% by weight - V 1% by weight - Mo 9% by weight, hydrogen reduction sintering method) Electrolytic Cu powder with a particle size of 45 μm, V powder with a particle size of 45 μm, and Mo powder with a particle size of 3 μm were used as the raw material particles. The material particles were weighed to be Cu 90% by weight, V 1% by weight, and Mo 14% by weight, and mixed in a ball mill for 3 hours. After mixing, the mixture was filled into a die and pressed at 50 MPa to form a green compact. The bulk density of the green compact was 55%.

[0058] The green compact was placed in a resistance heating furnace filled with high-purity hydrogen gas, heated at 500°C for 5 hours, and then cooled to 100°C. The furnace was then purged with nitrogen and cooled for 10 -3 The sintered body was placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 76%. Next, the sintered body was placed in a die and pressed at 400 MPa. The density of the sintered body after pressing was 76%. -3 The sintered body was placed in a resistance heating furnace set to a vacuum level of the Pa range and heated at 1300°C for 10 hours to obtain a sintered alloy. The density of the sintered body after heating was 98%.

[0059] A part of the sintered body was cut and the cross section was observed and analyzed using a scanning electron microscope and an energy dispersive X-ray detector, and the initial V particles derived from the material particles had disappeared. Mo particles were dispersed with a particle size of 0.01 μm to 1 μm. A detailed analysis of the interface between the Mo particles and the Cu matrix revealed that V was dissolved in the Mo particles, and that V was dissolved in the Mo particles in a region up to 0.05 μm from the boundary surface of the Cu matrix with the Mo particles. V was not observed in the region in the Cu matrix more than 0.05 μm away from the boundary surface. The amount of residual oxygen was measured by the inert gas fusion-infrared absorption method and found to be 60 ppm. The maximum interrupting current was measured by the same method as in the comparative example and found to be 0.8. The dielectric breakdown voltage was 0.9. Although the performance as a contact material for a vacuum valve was somewhat inferior to that of Comparative Example 1, the hydrogen reduction sintering method allows for mass production and is low cost, so the overall evaluation was △. The results are shown in Table 1 below.

[0060] Comparative Example 3 (Cu 75% by weight - V 5% by weight - Mo 20% by weight, vacuum sintering method) Electrolytic Cu powder with a particle size of 45 μm, electrolytic Cr powder with a particle size of 75 μm, and Mo powder with a particle size of 3 μm were used as raw material particles. The material particles were weighed to be Cu 75 wt% - Cr 5 wt% - Mo 20 wt% and mixed in a ball mill for 3 hours. After mixing, the mixture was filled into a die and pressed at 50 MPa to form a green compact. The bulk density of the green compact was 53%. 10 -3 The green compact was placed in a resistance heating furnace set to a vacuum level of the order of Pa and heated at approximately 1000°C for 5 hours. The density of the sintered compact after heating was 79%. The sintered compact was placed in a die and pressed at 400 MPa. The density of the sintered compact after pressing was 85%. The compact was then heated for 10 -3 The sintered body was placed in a resistance heating furnace set to a vacuum of the Pa range, and was further heated at about 1100°C for 5 hours. The density of the sintered body after heating was 95%.

[0061] A part of the sintered body was cut and the cross section was observed and analyzed using a scanning electron microscope and an energy dispersive X-ray detector, and it was found that 20μm to 70μm Cr particles and 0.1μm to 3μm Mo particles were dispersed in the Cu matrix. A detailed analysis of the interface between the Mo particles and the Cu matrix revealed that the Mo particles and the Cu matrix had a purity of 99% or more and no Cr was present. The amount of residual oxygen was measured by the inert gas fusion-infrared absorption method and was found to be 1700ppm. The maximum interrupting current value was measured by the same method as in the comparative example and was found to be 0.7. The dielectric breakdown voltage was 0.9. The amount of residual oxygen was large and the performance as a contact material for a vacuum valve was also inferior to that of Comparative Example 1, so the overall evaluation was x. The results are shown in Table 1 below.

[0062] Comparative Example 4 (Example of Electric Current Sintering Method) Electrolytic Cu powder with a particle size of 45 μm, electrolytic Cr powder with a particle size of 75 μm, and Mo powder with a particle size of 3 μm were used as raw materials. The material particles were weighed to be Cu 75 wt%, Cr 5 wt%, and Mo 20 wt%, and mixed in a ball mill for 3 hours. After mixing, the mixture was filled into a graphite die and placed in a vacuum chamber. The vacuum chamber was depressurized to the 1 Pa range, and the powder filled in the die was pressurized using a pressure module. A pulse current was applied from the electrodes installed in the die, and the applied pulse was adjusted so that the die surface temperature was approximately 800°C, after which it was held for 10 minutes and sintered. The density of the sintered body after sintering was 92%.

[0063] A part of the sintered body was cut and the cross section was observed and analyzed using a scanning electron microscope and an energy dispersive X-ray detector, and it was found that 20μm to 70μm Cr particles and 0.1μm to 5μm Mo particles were dispersed in the Cu matrix. A detailed analysis of the interface between the Mo particles and the Cu matrix revealed that the Mo particles and the Cu matrix had a purity of 99% or more and no Cr was present. The amount of residual oxygen was measured by the inert gas fusion-infrared absorption method and was found to be 5500ppm. The maximum interrupting current value was measured by the same method as in the comparative example and was found to be 0.6. The dielectric breakdown voltage was 0.8. The amount of residual oxygen was large and the performance as a contact material for a vacuum valve was also inferior to that of Comparative Example 1, so the overall evaluation was x. The results are shown in Table 1 below.

[0064] [Table 1]

[0065] Although some embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims. [Explanation of symbols]

[0066] 6, 7...contact, 5, 8...electrode, 20...contact material for vacuum valve, 21, 21-1...Cu matrix, 22, 22-1...filler, 23...surrounding region, 25...interface, 100...vacuum valve

Claims

1. A copper matrix; A filler containing molybdenum; A contact material for a vacuum valve comprising a sintered alloy containing at least one of chromium and vanadium as a sintering aid.

2. 2. The vacuum valve contact material according to claim 1, wherein the copper content is 75 to 85% by weight, and the combined content of the molybdenum and the sintering aid is 15 to 25% by weight, based on the total weight of the sintered alloy.

3. 2. The vacuum valve contact material according to claim 1, wherein the filler has a volume-based median diameter of 0.01 μm to 10 μm.

4. 2. A contact material for a vacuum valve according to claim 1, wherein the oxygen content of said sintered alloy is in the range of 10 ppm to 1000 ppm.

5. 5. A vacuum valve comprising an electrode including a contact made of the vacuum valve contact material according to claim 1.

6. A mixture containing copper particles, molybdenum particles, and sintering aid particles of at least one of chromium and vanadium is compressed to form a green compact; heating the green compact in a hydrogen atmosphere; and and sintering the heated green compact.

7. The method of claim 6 , wherein the hydrogen atmosphere is high purity hydrogen gas.

8. 7. The method of claim 6, further comprising, after heating in the hydrogen atmosphere, flushing the heated green compact with a replacement gas prior to sintering.

Citation Information

Patent Citations

  • Contact material for vacuum valve and manufacturing method thereof

    JP3597544B2